Asymmetric Knee Kinematics And Kinetics After ACL Reconstruction In Adolescent Athletes. Issue 7 (29th July 2014) - Milewski, Matthew David; Ounpuu, Sylvia; Nissen, Carl W.; Garibay, Erin J.; Giampetruzzi, Nicholas; Suprenant, Danielle; Woods, Jessica R.
Objectives: To compare the kinematics and kinetics between the reconstructed anterior cruciate ligament (ACLR) and healthy knees of adolescent athletes that have been returned to sport (RTS) following standard protocols. Methods: Adolescent athletes completed our institution's RTS assessment which included the following tasks: running, drop vertical jump (DVJ), single leg long hop (SLLH), triple hop (TH) and cross-over triple hop (CTH), while simultaneous three-dimensional motion capture was performed using a VICON MX motion capture system (Vicon Motion Systems Inc., Los Angeles, CA) and three force platforms (AMTI, Advanced Medical Technology Inc, Watertown, MA) following standard techniques. The sagittal knee kinematics, internal moments and powers of a patient's ACLR knee were compared to their uninjured knee during the landing phase of each task. Asymmetry was defined as differences greater than 10% between the ACLR and uninjured knee. Results: At the time of the evaluation, 10 of 16 patients (three females and seven males, mean age 15.4 ±1.8 years old) were allowed to RTS following institutional guidelines. All patients were at least 6 months post ACL reconstruction. Motion analysis showed the ACLR knee had a greater than 10% deficit for peak knee flexion in running, SLLH, TH and CTH for 5/10, 7/10, 5/10 and 6/10 patients, respectively. The ACLR knee also had a greater than 10% deficit for peak knee extensor moment in running, DVJ, SLLH, TH and CTH for 7/10, 7/10, 7/10, 7/10 and 7/10 patients, respectively. The ACLR knee also had a greater than 10% deficit for peak power absorption in running, DVJ, SLLH, TH and CTH for 6/10, 6/10, 5/10, 6/10 and 6/10 patients, respectively. Paired Student T-tests showed statistically significant differences between the ACLR knee and the uninjured knee for selected variables in running, DVJ, SLLH, TH and CTH (Table 1). Conclusion: Athletes in this study showed frequent asymmetry (greater than 10% deficit on the ACLR side) in knee kinematics and kinetics during running, jumping and hopping after RTS approval following standard assessments. Mean peak knee flexion, moment and power values, were lower on the ACLR side in running and all jumps and statistically significantly lower on the ACLR side in 9/15 comparisons. The reduced peak knee extensor moment and power absorption computed on the ACLR knee in comparison to the healthy knee during these functional tasks may predispose the healthy knee to injury due to continued higher loads or predispose the ACLR knee to increased weakness over time due to continued decreased loads. Long-term follow-up to evaluate whether these asymmetries continue to increase may help explain increased ACL re-rupture or contralateral ACL injury rates in this population. If these asymmetries in kinematics and kinetics link to possible injury risk, RTS decision-making may benefit from knowledge of these objective measures.